A double‐blind, randomized, placebo‐controlled, parallel study to evaluate the efficacy and safety of imidafenacin in patients with overactive bladder in Taiwan. Issue 1 (25th August 2020) - Chuang, Yao‐Chi; Lin, Chih‐Chieh; Chow, Po‐Ming; Lien, Chi‐Shun; Tsui, Ke‐Hung; Chou, Chieh‐Lung; Lee, Hsiang‐Ying; Meng, En; Kuo, Hann‐Chorng
Abstract: Objective: This study evaluated the efficacy and safety of imidafenacin 0.1 mg twice daily vs placebo for Taiwanese patients with overactive bladder (OAB) after a 12‐week oral administration. Methods: This randomized, double‐blind, placebo‐controlled, two‐arm, parallel‐group, prospective study enrolled 118 patients across 11 study sites in Taiwan. Subjects were randomized to imidafenacin or placebo in a 2:1 ratio and entered the 12‐week treatment period. At the subsequent visits, efficacy outcome measures and safety assessments were collected for analysis. The primary efficacy outcome was the change in the mean number of micturitions per day. Secondary endpoints included mean changes from baseline in urgency episodes and urge incontinence episodes per day and mean volume voided per micturition. Safety outcomes were also collected and compared between groups. Results: A total of 78 and 40 patients were allocated to the imidafenacin and placebo groups, respectively. Among them, 100 patients (imidafenacin, 65 and placebo, 35) completed the trial. Compared with placebo, imidafenacin was significantly better at reducing the number of micturitions per day (−1.29 ± 2.23 vs ‐0.46 ± 3.49, P = .0171) and reducing the mean number of urge incontinence episodes (−0.15 ± 0.52 vs 0.04 ± 0.50, P = .0386) at week 12. Adverse events were reported in 35 subjects (44.9%) and 16 (40%) in the imidafenacin and placebo groups, including constipation (n = 3, 4), dry mouth (n = 11, 2), and urinary tract infection (n = 7, 4), respectively. One patient in the imidafenacin group had mild dysuria. Conclusion: Imidafenacin demonstrated efficacy and safety in the treatment of OAB in Taiwanese patients.